(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
This research aims to analyze the forces that affect oil droplets to illustrate that augmenting the mass of an oil droplet fosters favorable conditions for interaction between displaced and displacing fluids. This, in turn, impedes the bypassing of the displacing fluid around the oil droplets. In this investigation, the concept of augmenting the mass of an oil droplet is realized through absorption phenomena, employing coated spinel oxide (cobalt ferrite oxide) nanoparticles (CFO NPs). The synthesis of CFO NPs was successfully carried out in the laboratory using a sol-gel technique, followed by coating with a surfactant and lauric acid. The coated spinel oxide NPs underwent characterization using IR, XRD, and XRF techniques. The procedures started with the calculation of capillary force restrictions for small and large oil droplets. Furthermore, practical experiments involving oil droplets on glass plates at a 30° angle were conducted for different scenarios: without water injection, with water injection, and during the "absorption effect" of CFO NPs. The findings revealed that a large oil droplet exhibits lower capillary pressure restrictions compared to a small oil droplet, with a disparity of 0.02 m/s2. Consequently, it is comparatively easier for large oil droplets to become free than small ones. Moreover, a large oil droplet exhibits faster movement than small oil droplets due to gravitational effects in the absence of any injections. During the water injection scenario, the water droplets were unable to displace the oil droplet; instead, they passed through the passage beside and above the oil droplet consistently with an increase in the amount of water droplets. However, in the coated CFO NPs scenario, absorption of the coated CFO NPs onto the oil droplet was observed. This resulted in the aggregation of oil molecules, augmenting the gravity of the oil droplet and creating favourable conditions for its displacement. Notably, no water bypass beside the oil droplet was observed in this scenario, unlike the water scenario. Additionally, the aggregation of oil molecules induced corner flow, providing conducive conditions for microemulsion formation, altering wettability, modifying residual oil saturation, and enhancing injection performance. Euler’s equation was employed to analyse corner flow, indicating that the level of oil deformation increases with the rising rotation velocity, potentially leading to an increased recovery factor.